Facile Preparation of Chitosan‐modified Mesoporous Titanium Dioxide Film on Fused‐silica Capillary for Selective Enrichment of Phosphopeptides. Issue 2 (8th December 2021) - Lv, Xinyan; Jiao, Shihui; Cui, Lili; Wei, Zhonglin; Wang, Boran; Wang, Wenwen; Zhang, Qi; Tan, Yumei; Pang, Guangsheng; Feng, Shouhua
Abstract: Chitosan (Cts), a positively charged natural polysaccharide, is employed to functionalize mesoporous titanium dioxide (mTiO2 ) nanoparticles. The prepared Cts/mTiO2 composite was used as a stationary phase to coat the inner wall of fused‐silica capillary and obtain uniform Cts/mTiO2 film. The Cts/mTiO2 film is applied to detect and enrich phosphopeptides in complex biological samples based on typical in‐tube solid phase microextraction (IT‐SPME) system. This unique Cts/mTiO2 film exhibits excellent enrichment performances of high selectivity ( β ‐casein and BSA in molar ratio of 1 : 1000), sensitivity (detection limit as low as 40 fmol of β ‐casein tryptic digest solution) and high adsorption capacity (124.5 μg mg −1 ). Meanwhile, the Cts/mTiO2 film possesses preferable reusability and can be reused more than 10 times. These results confirm that the Cts/mTiO2 film possesses potential and satisfactory prospects in phosphoproteomics analysis. Abstract : A chitosan functionalized mesoporous titanium dioxide (Cts/mTiO2 ) film coated on the inner wall of fused‐silica capillary is employed for selective detection and enrichment phosphopeptides based on typical in‐tube solid‐phase microextraction.